CKM Glu83Gly Is Associated With Blunted Creatine Kinase Variation, but Not With Myalgia. (August 2017) - Siddiqui, Moneeza Kalhan; Veluchamy, Abirami; Maroteau, Cyrielle; Tavendale, Roger; Carr, Fiona; Pearson, Ewan; Colhoun, Helen; Morris, Andrew D.; George, Jacob; Doney, Alexander; Pirmohamed, Munir; Alfirevic, Ana; et al.
Abstract : Background—: To test the association of a recently reported variant in the creatine kinase (CK) muscle gene, CKM Glu83Gly (rs11559024) with constitutive creatine phosphokinase (CK) levels, CK variation, and inducibility. Given the diagnostic importance of CK in determining muscle damage, we tested the association of the variant with myalgia. Methods and Results—: Meta-analysis between longitudinal cohort GoDARTS (Genetics of Diabetes Audit and Research, Tayside Scotland), minor allele frequency (=0.02), and randomized clinical trial (JUPITER [Justification for the Use of Statins in Primary Prevention: An Intervention Trial Evaluating Rosuvastatin], minor allele frequency=0.018) was used to replicate the association with baseline CK measures. GoDARTS was used to study the relationship with CK variability. Myalgia was studied in JUPITER trial participants. Baseline and SDs of CK were on average 18% ( P value=6×10 −63 ) and 24% ( P value=2×10 −5 ) lower for carriers of the variant, respectively. The variant was not associated with myalgia (odds ratio, 0.84; 95% confidence interval, 0.52–1.38). Conclusions—: This study highlights that a genetic factor known to be associated with constitutive CK levels is also associated with CK variability and inducibility. This is discussed in the context of evidence to suggest that the variant has an impact on inducibility of CK by trauma through a previously reported case of a homozygous carrier. However, the lack of association between the variant and myalgia suggests that it cannot reliably be used as a biomarker for muscle symptoms. Abstract : Supplemental Digital Content is available in the text.